Atributos do solo em áreas sob cultivo sucessivo de arroz de terras altas em semeadura direta: efeitos sobre a produtividade - França, Sinnara Gomes de Godoy (2013)
Upland rice cultivation under no-tillage has shown low productivity when compared to conventional tillage, requiring further technological adjustments. This study aimed to identify which attributes of an Oxisol of the Cerrado are most affected by successive rice crops under no-tillage and which is the set of these attributes that correlates to rice yield, in order to establish the most suitable soil conditions for this crop. In February 2011, in areas cropped with upland rice under no-tillage system by one, two and three years, respectively, at Santo Antônio de Goiás, GO, rice grain yield was determined and soil samples were taken from soil layer of 0.00 - 0.10 m of an Acric Red Latosol to determine soil physical, chemical and biological attributes. Multivariate analysis techniques were applied on data obtained and it showed that rice crops cause changes in all soil attributes compared to the forest, with the exception of K and Cu contents, metabolic and microbial (qMIC) quotients and microbial biomass N: total N relationship (MBN:N). These attributes and Mn content are responsible for discriminating the areas under successive rice crops. The physical attributes are very similar among areas. Cu and Mn contents are higher in the area with one year of rice cultivation, as well as qMIC and MBN: N. The metabolic quotient increases with the years of rice cultivation, which indicates an increase in stress or disorder condition in the soil microbiota. Rice grain yield is positively correlated with total nitrogen, copper, iron, manganese, microbial biomass carbon and nitrogen contents, total enzymatic and acid phosphatase activities, microbial quotient and MBN:N relationship, and negatively correlated with microporosity and metabolic quotient. Based on multiple linear regression analysis, the soil attributes that together better explain the grain yield were copper, iron and microbial biomass nitrogen contents and acid phosphatase activity.